Positron extraction to an electromagnetic field free region. (24th November 2015) - Cooke, D A; Barandun, G; Vergani, S; Brown, B; Rubbia, A; Crivelli, P
Abstract: We describe a scheme for high efficiency ( ) extraction of 50 ns positron bunches from a buffer gas trap in an electromagnetic field free region. The positrons are time bunched to approximately 1 ns (FWHM) and focussed to less than 1 mm ( σ ). The target is kept at ground potential which is an advantage for many applications. The results compare well with SIMION simulations.